Assessment of meal induced gastric accommodation by a satiety drinking test in health and in severe functional dyspepsia. Issue 9 (11th August 2003) - Tack, J; Caenepeel, P; Piessevaux, H; Cuomo, R; Janssens, J
Abstract : Aims: Impaired gastric accommodation is a major pathophysiological mechanism in functional dyspepsia. The aim of the present work was to assess a satiety drinking test in the evaluation of accommodation in health and dyspepsia. Methods: Twenty five controls and 37 severely dyspeptic patients seen at a tertiary care centre completed a dyspepsia questionnaire, and gastric emptying and gastric barostat studies. The amount of liquid meal ingested at maximum satiety during a slow satiety drinking test was determined. In controls, we studied the influence of caloric density and of pharmacological agents that influence accommodation. Results: In patients, satiety scores were higher and maximum satiety occurred at lower calories (542 (50) v 1508 (53) kcal; p<0.0001). Six patients had required nutritional support, but excluding these did not alter the correlations. With increasing severity of early satiety, less calories were ingested at maximum satiety. In multivariate analysis, the amount of calories was significantly correlated to accommodation but not to gastric emptying or sensitivity. Sensitivity and specificity of the satiety test in predicting impaired accommodation reached 92% and 86%, respectively. At different caloric densities, ingested volume rather than caloric load determined maximum satiety. Pharmacological agents (sumatriptan, cisapride, erythromycin) affected the satiety test according to their effect on accommodation. Conclusion: A slow caloric drinking test can be used to evaluate accommodation and early satiety. It provides a non-invasive method of predicting impaired accommodation and quantifying pharmacological influences on accommodation.